EFEKTIFITAS PERMAINAN LEGO TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK PRASEKOLAH DI MASYARAKAT - Yasmin Yulia Gempita; Ganis " Indriati; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Fine motor development is the aspect that relating to the ability of children to do movement of the small muscles. This study aims to determine the effectiveness of lego game toward the development of fine motor skills of preschool children in the community. The method used in this study is quasi-experimental with pre-test and post-test design with control group. The study was done in Tuah Karya, Tampan, Pekanbaru  with  30 respondents taken by purposive sampling technique. Respondents were divided into two groups: experiment and control groups. Experiment group was the group that was given the lego game while the control group was given no intervention. Instruments of measuring used  denver Development Screening Test (DDST). Data were analyzed  by using univariate and bivariate analysis. Univariate analysis describes the characteristics of the respondent and bivariate analysis explain the relationship to between the variables by using chi-square test. The results of this study indicates that the lego game is effectiveto  toward to increase fine motor development of preschool children fine motor in community (p value  0.00). The results of this study  recommends the parents or caregiver  to provide  stimulus for a better growth and development. Keyword: development, effectiveness, lego, preschool, fine motor